Islamic Communication Strategy in Facing AI Disinformation in Padangsidimpuan City: Digital Literacy and Critical Thinking of the Young Generation - Ahmad Sultoni (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The development of Artificial Intelligence (AI)-based technology has increased the production and spread of disinformation in the digital space, posing serious challenges for the younger generation in identifying the veracity of information. This study aims to analyze how Islamic communication strategies can contribute to improving the digital literacy and critical thinking skills of the younger generation in dealing with AI disinformation in Padangsidimpuan, North Sumatra. The study used a qualitative approach with a case study design through in-depth interviews, limited observation, and documentation with eleven informants consisting of religious scholars, digital communication experts, educators, and young social media users. Data analysis was conducted thematically using an interactive analysis model. The results show that the application of Islamic communication principles such as tabayyun (religious inquiry), qaulan sadidan (verification of information), and the ethics of information verification can strengthen digital literacy and encourage critical thinking among the younger generation in evaluating digital information. Furthermore, the role of religious scholars and educators as opinion leaders contributes to building the younger generation's epistemic awareness of the dangers of AI disinformation. This study concludes that integrating Islamic communication values ​​with digital literacy can be an effective strategy in increasing the resilience of the younger generation to information manipulation in the era of artificial intelligence. The authors recommend further research to quantitatively examine the effectiveness of Islamic communication strategies in improving digital literacy. The study also needs to be expanded to include formal education, digital communities, and social media. Furthermore, it is crucial to examine the use of AI technology as an educational tool to sustainably strengthen digital literacy based on Islamic values.